2018
DOI: 10.1002/jaal.758
|View full text |Cite
|
Sign up to set email alerts
|

Why the “Struggling Reader” Label Is Harmful (and What Educators Can Do About It)

Abstract: The authors featured in this department column share instructional practices that support transformative literacy teaching and disrupt “struggling reader” and “struggling writer” labels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Another, equally important but not frequently talked about aspect of responsiveness is teachers’ understanding of the reading process as it relates to specific populations of students. This aspect of responsiveness acknowledges that the frameworks that teachers hold of particular students and how they engage in the reading process in turn shape teachers’ interactions with them (Frankel & Brooks, 2018). For example, if teachers primarily view emergent bilinguals as English learners, then their instruction will emphasize language learning, such as teaching new vocabulary and phrases during reading instruction.…”
Section: Responsive Reading Instruction For Emergent Bilingualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another, equally important but not frequently talked about aspect of responsiveness is teachers’ understanding of the reading process as it relates to specific populations of students. This aspect of responsiveness acknowledges that the frameworks that teachers hold of particular students and how they engage in the reading process in turn shape teachers’ interactions with them (Frankel & Brooks, 2018). For example, if teachers primarily view emergent bilinguals as English learners, then their instruction will emphasize language learning, such as teaching new vocabulary and phrases during reading instruction.…”
Section: Responsive Reading Instruction For Emergent Bilingualsmentioning
confidence: 99%
“…Grounding teachers’ understanding of reading instruction in a deep understanding of students is critical. Although emergent bilinguals are often positioned as struggling readers when viewed from a position of deficit (Frankel & Brooks, 2018; Martínez, 2018), their bilingualism and bilingual identities can be a critical element in the development of their reading processing systems.…”
Section: Supporting the Emergent Bilingual Reader In Guided Readingmentioning
confidence: 99%
“…In our professional and personal lives, we have seen how certain adolescents identified as English learners (ELs) and struggling readers are positioned as having limited literacy abilities (Brooks, ; Frankel, ). Moreover, we have observed that common instructional settings for adolescents identified as ELs are compulsory reading intervention courses that specifically identify these students as struggling readers, with all the deficit perspectives that accompany this label (e.g., Brooks, ; Callahan, ; Frankel & Brooks, ; Gomez, ; Wu & Coady, ). We are concerned that these intersecting labels and instructional settings can serve to mask the linguistic and literate abilities of this student population.…”
mentioning
confidence: 99%
“…Here, we use a selection of articles published in JAAL to show how adolescents’ social media and other digital literacy practices can provide a pathway for educators to build on students’ transnational knowledge bases. Previously, we argued that this type of instruction is fundamental to challenging deficit notions that are inherent to the struggling reader label (Frankel & Brooks, ).…”
mentioning
confidence: 99%
“…Students discuss their responses in their groups. I n this department's inaugural column, coeditors Frankel and Brooks (2018) urged educators to take a critical stance toward the labels that so commonly define adolescent and adult readers. A recommendation for how to do this was to engage in practices that represent a developmental understanding of reading as situated practice, one that is fostered through the coconstruction of collaborative learning environments and disrupts the traditional teacher-student relationship.…”
mentioning
confidence: 99%